Kant’s Aesthetics and the Problem of Aesthetic Judgement in Music - Pascual, Luciano (2022)
This paper reconstructs the place of music in the division of the arts proposed by Kant in his third Critique, focusing on the aspects that make music an art difficult to characterise. For this purpose, it exposes the foundations that allow situating music at the highest levels of Kant’s incipient system of the arts, as well as the reasons that allow placing it on the lowest ones. In addition, the paper approaches the problem of the pendular place of music as a beautiful art and as an agreeable art, recovering and contrasting different passages of Kant’s Critique of Judgement. To complement this last aim, readings from different thinkers are reviewed, considering, on the one hand, those who claim that Kant characterises music as a beautiful art, and, on the other hand, those who claim that he characterises it as a mere agreeable art. Finally, this paper presents the conclusions that allow to understand that music’s double possibility, as a beautiful and as agreeable art, depends on the ways in which the subject relates to music.